2016
DOI: 10.7287/peerj.preprints.1807v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examination of antimicrobial activity of selected non-antibiotic products

Abstract: A variety of pharmaceutical preparations, which are applied in the management of non-infectious diseases, have shown in vitro some antimicrobial activity. These drugs are called "non-antibiotics". So far, a lot of attention has been focused on phenothiazines, thioxanthenes and other agents with affinities to cellular transport systems or agents showing other inhibition mechanism. Several authors confirmed that some nonantibiotics are "helper compounds", which enhance the in vitro activity of certain antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…4 ). The mechanism behind the effects of telmisartan on microbiota can only be speculated upon but could reflect the selective antimicrobial potential previously associated with telmisartan (Kruszewska et al 2002 ). While the causal relationship to atherosclerosis inhibition is not known, these crude profiles of the predominant endogenous gut bacteria indicate that further studies with more thorough methodology are warranted to investigate whether the beneficial effects of VSL#3 were mediated via compositional modulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). The mechanism behind the effects of telmisartan on microbiota can only be speculated upon but could reflect the selective antimicrobial potential previously associated with telmisartan (Kruszewska et al 2002 ). While the causal relationship to atherosclerosis inhibition is not known, these crude profiles of the predominant endogenous gut bacteria indicate that further studies with more thorough methodology are warranted to investigate whether the beneficial effects of VSL#3 were mediated via compositional modulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…One report showed minimum inhibitory concentrations (MIC) in the range of 5-10,000 lg/ml for gram-positive and gram-negative organisms as part of a quality control report. 21 A conference abstract reported alendronate MIC of 100-800 mg/L for a panel of gram-negative organisms. 22 In a periodontitis rat model, it was also reported that sodium alendronate inhibited growth of Fusobacterium nucleatum and Peptostreptococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…MTX is a structural analog of folic acid that can competitively inhibit the binding of dihydrofolic acid to the enzyme dihydrofolate reductase, thereby interfering with purine and pyrimidine metabolism and therefore inhibiting DNA and RNA synthesis, DNA repair, and cell division. MTX has been found to be bacteriostatic in vitro against Staphylococcus aureus (but not against E. coli and Pseudomonas aeruginosa ) [51].…”
Section: Correlation Between the Gut Microbiome And Autoimmune Uveitismentioning
confidence: 99%